Analysis of Determinants of Laboratory Equipment Operational Cooperation System Based on Cost Benefit Analysis in Hospital Management Perspective in X - Kemalayanti, Nursep; Firdawati, Firdawati; Semiarty, Rima (Newinera Publisher, 2025)
Procurement of laboratory equipment through operational cooperation is increasingly adopted by hospitals as a cost-effective and efficient strategy to support health services. This study examines the success of operational cooperation in procuring hematology analyzer equipment to replace damaged units, using a cost-benefit analysis (CBA) from the perspective of hospital management. Employing a sequential explanatory mixed-method approach, the study combined qualitative data from in-depth interviews with 12 purposively selected informants and observations, with quantitative analysis of secondary data using the CBA method. The analysis revealed a positive Net Present Value (NPV) of IDR 99,422,367.47 and a Benefit-Cost (B/C) ratio of 1.59, both exceeding the benchmarks of independent procurement. This indicates that operational cooperation is financially feasible and preferable. Non-financial benefits also strengthen this conclusion, including vendor-provided maintenance technicians, guaranteed supply of reagents and spare parts, and ongoing equipment upgrades aligned with technological advancements. These advantages minimize hospital disruptions and ensure service continuity. The study identifies key success determinants in the operational cooperation system: cost efficiency, human resources, regulatory compliance, vendor partnerships, equipment quality, historical laboratory data, and alignment with technological developments. In conclusion, operational cooperation for hematology analyzers is successful, sustainable, and offers significant benefits, both financial and operational, for hospitals.